Effectiveness Of The Use Of Technology In The Development Of Marketing Strategies In The Company - Masruri, Masruri; Sutarjo, Sutarjo; Surya, Rahadiyan; Widagdo, Djoko; Muliyati, Muliyati (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In today's increasingly competitive business environment, developing Information Technology is having a major impact on the Company's ability to compete. In order for the company to be competitive, the company must continuously keep pace with the development and progress of information technology. The use of economic criteria with measures of effectiveness, efficiency and productivity is one of the advantages of the competitiveness of the company. Information technology implementations are designed to increase the effectiveness, efficiency and productivity of people and organizations to generate targeted margins with minimal risk and cost.